INSTITUTIONAL REFORMS IN THE WATER MANAGEMENT SYSTEM OF UZBEKISTAN AND THEIR EFFICIENCY (Modern American Journal of Social Sciences and Humanities, 2026)
This article analyzes the institutional reforms implemented in the water management system of the Republic of Uzbekistan during the post-independence period, their legal foundations, governance mechanisms, and effectiveness. The achievements and remaining problems in the Kashkadarya oasis are examined as a case study. The research results show that the basin principle of water resource management, the system of Water Consumers' Associations (WCAs), digitalization processes, and the introduction of economic mechanisms have played an important role. At the same time, existing problems in the system are identified, and proposals for their elimination are put forward.